Keabsahan Akta Notaris yang Menggunakan Cyber Notary Sebagai Akta Otentik - Zaenul Islam, Ahmad; Kurniawan, Kurniawan; Hirsanuddin, Hirsanuddin (Universitas Ekasakti, 2023)
The rapid development of information technology can enable Notaries in carrying out their positions to interact indirectly with interested parties. This research is normative legal research which aims to analyze the concept of cyber notary as an authentic deed in Indonesia and the validity of notarial deeds that use cyber notary as authentic deeds. The results of this research are: The cyber notary concept is a concept that utilizes technological advances for notaries in carrying out their duties, such as: digitizing documents, signing deeds electronically, holding General Meeting of Shareholders (GMS) via teleconference. The validity of notarial deeds using Cyber ​​Notary is based on Article 16 paragraph (1) letter m UUJN in its explanation that the Notary must be physically present and sign the deed simultaneously with the presenters and witnesses. So the validity of the cyber notary as an authentic deed cannot yet be said to be authentic.